Microstructure and Dynamic Properties of Aggrecan Assemblies. (10th January 2018) - Horkay, Ferenc; Basser, Peter J.; Hecht, Anne-Marie; Geissler, Erik
ABSTRACT: The effect of ions on the structure and dynamics of aggracan solutions was investigated using a variety of scattering techniques (neutron spin echo, small angle neutron scattering, static and dynamic light scattering). The results show that aggrecan forms microgel-like assemblies which remain stable in the presence of counter-ions. As opposed to many synthetic polyelectrolytes which exhibit a great sensitivity to ion concentration and charge valency, it was found that aggrecan solutions are remarkable insensitive to charge valence. This property of aggrecan is consistent with its biological role as an ion reservoir mediating calcium metabolism and maintaining dimensional stability in cartilage and bone.